PENGARUH METODE EKSPERIMEN TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DI KELAS V SD - Febri Dwi Lestari; Hery Kresnadi; Siti Halidjah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to identify the effect of experimental method on student learning outcomes in 5th grader of State Sekolah Dasar Negeri 56 Pontianak Barat. Quasi-experimental method with the Non Equivalent Control Group Design was applied in conducting this study. The population of this study were 5th grader of State Sekolah Dasar Negeri 13 Pontianak Barat, 5th grader of State Sekolah Dasar Negeri 54 Pontianak Barat and 5th grader of State Sekolah Dasar Negeri 56 Pontianak Barat. The chosen sample was the 5th grader of State Sekolah Dasar Negeri 56 Pontianak Barat, which consists of two classes. Class A (30 students) as the experimental class, while Class B (32 students) as the control class. The technique of data collection was measuring technique through 40 multiple choice questions as the data collection tools. Then, the analysis was calculated by using t-test. The results showed tcount (2.0526) > ttable (1.671) which means Ha is accepted. Therefore, it can be concluded that learning outcomes will be different between students who treated through the Experiment Method and they who did not. The effect size calculation showed that ES in position of 0.52 (medium criteria). It means learning through Experimental Method gives a moderate effect on student learning outcomes in the 5th grader of State Sekolah Dasar Negeri 56 Pontianak Barat. Keywords: Effect, Experimental Method, Learning Outcomes